2013
DOI: 10.1161/circoutcomes.112.967356
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Identified Factors Related to Heart Failure Readmissions

Abstract: Background Although readmission following hospitalization for heart failure (HF) has received increasing attention, little is known about its root causes. Prior investigations have relied on administrative databases, chart review, and single-question surveys. Methods and Results We performed semi-structured 30-60 minute interviews of patients (n=28) readmitted within 6 months of index HF admission. Established qualitative approaches were used to analyze and interpret data. Interview findings were the primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
95
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(105 citation statements)
references
References 23 publications
9
95
0
1
Order By: Relevance
“…This 18 and many readmissions are not easily attributable to a single cause. 1,19 Therefore, even if the three domains of the CTM-3 were addressed equally for patients with PCI and CABG, their post transition experiences and ultimate reasons for readmission could vary greatly. Although our study generally supports the association between the CTM-3 score and readmission, it should be interpreted with caution, and the association should be validated on a large scale, at the hospital level in future studies.…”
Section: And Readmissionmentioning
confidence: 99%
“…This 18 and many readmissions are not easily attributable to a single cause. 1,19 Therefore, even if the three domains of the CTM-3 were addressed equally for patients with PCI and CABG, their post transition experiences and ultimate reasons for readmission could vary greatly. Although our study generally supports the association between the CTM-3 score and readmission, it should be interpreted with caution, and the association should be validated on a large scale, at the hospital level in future studies.…”
Section: And Readmissionmentioning
confidence: 99%
“…Patients often did not seek care until symptoms became intolerable [55,51,67,59,56,72,74]. Frightening attacks of acute breathlessness were the most common reason patients sought professional care [51,49,56,74].…”
Section: "I Don't Know Really; I'm So Used To It Now" [71]mentioning
confidence: 99%
“…In other cases, patients perceived the ability of local physicians was inadequate for HF specific management [56]. Many noted a preference for doctors in the ER, with specialist HF knowledge.…”
Section: Perceived System and Provider Barriers To Accessing Carementioning
confidence: 99%
“…Prior studies suggest that, in general, patients and caregivers attribute failed transitions to a lack of preparedness for discharge, [14][15][16][17] a sense of exclusion from discussions of the care plan, 14,18 abandonment by the health care system after discharge 15,19 and lack of adherence to discharge recommendations. 20,21 Despite the fact that low-SES patients are at higher risk for poor outcomes, few prior studies specifically explore the perspectives of these patients. 22 One qualitative study of 21 patients served in lowincome community health centers suggested that low-SES patients knew their diagnoses, medications and discharge instructions, but faced other non-knowledge barriers to recovery such as stress, difficulty paying for home care and lack of transportation.…”
Section: Introductionmentioning
confidence: 99%